A glut of coconut? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
How about producing high quality coconut oil at home in 11/2 hours? Dan Etherington, an Australian agricultural economist, has developed Direct Micro Expelling (DME), a process using a cold pressing unit for making virgin coconut oil. More than 70...